Patient reaction to Tdap vaccination in pregnancy. Issue 23 (25th May 2017) - Perry, Jamie; Towers, Craig V.; Weitz, Beth; Wolfe, Lynlee
Abstract: Background: The current obstetrical recommendation is to routinely administer the tetanus, diphtheria, and acellular pertussis (Tdap) vaccination during every pregnancy regardless of a patient's prior history. There are minimal data that have prospectively evaluated solicited patient response to this treatment plan. The study objective was to evaluate patient reaction following receipt of Tdap vaccination during pregnancy. Methods: This was a prospective observational study conducted from May 2014 through March 2016. The study design involved solicited patient reaction within 1–7 days after the administration of the Tdap vaccine. Data collected included pain or soreness, swelling, and/or redness at the injection site, as well as, fever and generalized body aches. Statistical analysis involved simple percentages with Poisson binomial 95% confidence intervals with Chi-square and Fisher's exact comparisons where appropriate. Results: A total of 737 patients were evaluated and 496 (67%, 95% Confidence Interval [CI] 64–71%) were found to have at least 1 reaction to the vaccination and 187 (25%, 95% CI 22–29%) had 2 reactions or more. Overall, the majority of patients stated that the vaccination was tolerated. However, 24 (3%, 95% CI 2–5%) of the study population stated that they would not accept receipt of Tdap in a subsequent pregnancy because of the response that occurred in the current pregnancy. Conclusion: These data demonstrate that maternal reactions following receipt of Tdap are common (two-thirds of the study population). A potential concern is the finding that some patients might refuse a repeat vaccination in a subsequent pregnancy due to these reactions. If further research reveals similar findings, a pertussis only vaccine for pregnant patients might need to be evaluated.